Impact of maximal sprinting speed on very high-speed running distance, sprinting distance and peak sprinting speed during soccer matches - Papadakis, L.; Ispyrlidis, I.; Patras, K. (Trends in Sport Sciences, 2025)
Introduction: Player on-field performance is often dictated by tactical constraints such as positional demands, playing formation and match scoreline. However, the relationship between how fast players run during an actual match compared to how fast they are able to run under controlled testing conditions is not well established.